2018
DOI: 10.1016/j.jid.2017.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Tolerance of DNA Damage Induced by Chronic UVB Irradiation of the Human Genome

Abstract: Exposure to solar UVB radiation leads to the formation of the highly mutagenic cyclobutane pyrimidine dimers (CPDs), the DNA damage responsible for mutations found in skin cancer. The frequency of CPD formation and the repair rate of those lesions are two important parameters to determine the probability of UVR-induced mutations. Previous work has shown that chronic irradiation with sublethal doses of UVB radiation (chronic low-dose UVB radiation) leads to the accumulation of residual CPD that persists over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…If CPDs accumulated in hyperhotspots, these regions could serve as objective sentinels of prior exposure, quantifiable in small skin samples. CPDs are known to persist unrepaired for at least 1 wk in telomeres and heterochromatin of proliferating mammalian cells (8,72) and for over 1 mo in epidermal stem cells (73). The present study found that, indeed, class 2 hyperhotspot sites had accumulated CPDs in the days or weeks before the experiment began, presumably reflecting internal CPD production by chemiexcitation (31).…”
Section: Discussionmentioning
confidence: 99%
“…If CPDs accumulated in hyperhotspots, these regions could serve as objective sentinels of prior exposure, quantifiable in small skin samples. CPDs are known to persist unrepaired for at least 1 wk in telomeres and heterochromatin of proliferating mammalian cells (8,72) and for over 1 mo in epidermal stem cells (73). The present study found that, indeed, class 2 hyperhotspot sites had accumulated CPDs in the days or weeks before the experiment began, presumably reflecting internal CPD production by chemiexcitation (31).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments showed that UVB caused S-phase cell cycle arrest to prevent further DNA damage and minimize the likelihood of introducing gene mutations in daughter cells. An early mechanism involved in CPD repair is activation of the DNA damage checkpoint that activates cell cycle delay to allow efficient repair [6]. Nucleotide excision repair (NER) is an important repair system that can remove UV-induced photolesions in placental mammals [34].…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive exposure to UVB increases the cellular reactive oxygen species (ROS) level, resulting in strand breaks and hydroxylation of DNA bases [5]. UVB can induce cell cycle arrest and mutagenic DNA damage, such as formation of cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6-4) pyrimidone photoproduct [6, 7]. These changes have detrimental effects that include carcinogenesis, cell senescence, and other skin pathologies [8].…”
Section: Introductionmentioning
confidence: 99%
“…UVB (280–315 nm) irradiation causes direct DNA and RNA damage by inducing covalent bond formation between adjacent pyrimidines, leading to the generation of mutagenic photoproducts, such as cyclopyrimidine dimers and pyrimidine-pyrimidine (6-4) adducts [ 40 , 41 ]. Additionally, UVA (315–400 nm) causes indirect DNA damage through a photo-oxidative stress-mediated mechanism, resulting in the formation of reactive oxygen species, which interact with lipids, proteins, and DNA to generate intermediates that combine with DNA to form harmful adducts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%